The Effect of Charades Game Toward Students’ Vocabulary Mastery at the Ninth Grade Students of MTs Muhammadiyah Kubangkondang, Cisata, Pandeglang, Banten - Indonesia - Prinaldi Aditya; Ade Sudirman; Ari Fajria Novari (Journal of English Education Studies, 2025)
This research aims to investigates the effect of the Charades Game toward students’ vocabulary mastery at the ninth grade of MTs Muhammadiyah Kubangkondang in the academic year 2025/2026. The research employed a quasi-experimental design with a pre-test and post-test control group. A total of 36 students participated, with 18 students in the experimental group and 18 students in the control group. The experimental group was taught using the Charades Game, while the control group received instruction through a conventional method. Data were collected using a multiple-choice vocabulary test and analyzed through descriptive statistics, normality and homogeneity tests, and independent samples t-test. The Shapiro–Wilk test confirmed that the data were normally distributed, and Levene’s test indicated homogeneity of variances. The results of the independent samples t-test further confirmed a significant difference in post-test scores between the experimental and control groups (p = 0.038, Cohen’s d = 0.718), favoring the experimental group. It can be concluded that the Charades Game is an effective teaching strategy for enhancing vocabulary mastery among junior high school students. The research recommends integrating game-based learning into English language teaching to foster engagement, motivation, and improved learning outcomes.